How the social and environmental aspects affect hydro power permit applications : a case study of the county administrative board in Värmland, Sweden - Nieminen, Lotta (2018)
This study assess how the county administrative board in Värmland, Sweden, considers social aspects in their environmental decision-making processes. The research problem stems from a different view on how to utilize the natural resources of rivers and a general concern for the biological well -being in the water bodies due to hydro power. The study has been conducted with five application cases offered by Fortum Sweden, which were complemented with interviews from the county administrative board. The applications were concerning hydro operation in Värmland, sent in to their county administrative board (CAB). The result has been presented and analysed with theories of social license to operate (SLO) and social impact assessment (SIA). The study showed that the county administrative board of Värmland acts from a strongly legal aspect. The social aspect is not included in the decision-making process as there exists an imbalance of power in the mediation platform. The imbalance in power hinders the involved parties to engage in communication. Further studies could focus on the internal structure at the county administrative board of Värmland.